The Effects of a Standard Postoperative Rehabilitation Protocol for Arthroscopic Rotator Cuff Repair on Pain, Function, and Health Perception - Monesi, Roberta; Benedetti, Maria Grazia; Zati, Alessandro; Vigna, Daniela; Romanello, Domenico; Monello, Alberto; Rotini, Roberto (Joints, 2018)
Purpose There is still conflicting evidence to support postoperative rehabilitation protocols using immobilization following rotator cuff repair over early motion. The objective of the study was to evaluate the evolution of pain, shoulder function, and patients' perception of their health status up to 1 year after cuff rotator repair and a standard postoperative rehabilitation protocol consisting of 4 weeks of immobilization followed by a 2-week assisted controlled rehabilitation.Methods Descriptive, longitudinal, uncontrolled case-series study was performed on 49 patients who underwent arthroscopic rotator cuff repair following traumatic or degenerative lesions. VAS scale for pain, Constant–Murley score for function, and SF-12 score for quality of life were used as outcome measures and were administered before the rehabilitation treatment, at the end of the 2-week rehabilitation, 3 months, and 1 year after surgery.Results VAS pain score decreased significantly along the follow-up reaching almost a nil value after 1 year (0.2). Function as measured by Constant–Murley score had a significant improvement during follow-up, reaching a mean value of 84.6. The short form (SF)-12 score increased over time reaching 46.3 for the physical and 43.8 for the psychological dimension, respectively, at 1 year.Conclusion The present study confirmed an excellent outcome at 1 year after rotator cuff repair using a traditional 4-week immobilization followed by a 2-week rehabilitation protocol without evidence of tendon un-healing or re-tearing.Level of Evidence This is a level IV, therapeutic case series.
Keywords: pain; rotator cuff; repair; arthroscopy; rehabilitation